Peri-operative dexamethasone therapy and post-operative psychosis in patients undergoing major oral and maxillofacial surgery - Chethan Manohara Koteswara; Pritish Patnaik (Wolters Kluwer Medknow Publications, 2014)
A broad array of behavioral symptoms, including psychosis, can transpire post-operatively following a variety of surgeries. It is difficult to diagnose the exact cause of post-operative psychosis. We report three cases, which developed psychosis post-operatively after undergoing major oral and maxillofacial surgeries. All the three patients were administered dexamethasone peri-operatively. Dexamethasone is used to prevent or reduce post-operative edema. The exact dose of dexamethasone, which can cause psychosis, is unknown. It is important to raise awareness about this potential complication so that measures for management can be put in place in anticipation of such an event.